2019
DOI: 10.1159/000500295
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment with Topical Diphenylcyclopropenone for Three Cases of Anogenital Warts in Children

Abstract: Anogenital warts are caused by human papillomavirus types 6 and 11. They are rare in children, and treatment is difficult since conventional treatments are generally painful and require the patient to be anesthetized. Topical diphenylcyclopropenone (DPCP) is a contact immunotherapy used for treatments of recalcitrant warts and alopecia areata. We herein report 3 cases of anogenital warts in children successfully treated with topical DPCP. Our results suggest that topical DPCP may be a valuable option for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…All lesions were fully regressed after 6 months. 12 Also, Yen and his coworkers applied topical 0.1% DPCP solution once every 2 weeks for 2 months to a large condyloma acuminatum of Buschke and Löwenstein; the authors concluded that the treatment was well tolerated, and the lesion disappeared completely after 6 months. 8 On the other hand, Suh and his colleagues reported that the complete clearance of viral warts located on the hands, feet, and other sites was achieved in 82.9% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All lesions were fully regressed after 6 months. 12 Also, Yen and his coworkers applied topical 0.1% DPCP solution once every 2 weeks for 2 months to a large condyloma acuminatum of Buschke and Löwenstein; the authors concluded that the treatment was well tolerated, and the lesion disappeared completely after 6 months. 8 On the other hand, Suh and his colleagues reported that the complete clearance of viral warts located on the hands, feet, and other sites was achieved in 82.9% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…All lesions were fully regressed after 6 months. 12 Also, Yen and his coworkers applied topical 0.1% DPCP solution once every 2 weeks for 2 months to a large condyloma acuminatum of Buschke and Löwenstein; the authors concluded that the treatment was well tolerated, and the lesion disappeared completely after 6 months. 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for cutaneous warts, anogenital warts (condyloma acuminatum) can also be treated by DNCB [ 78 , 79 ], SADBE [ 45 ], and DPCP [ 29 , 80 ], offering an alternative treatment option besides local application of podophyllum resin and 5-fluorouracil (5-FU), electrodessication, cryotherapy, and laser therapy [ 78 ]. However, clinical trials on a larger scale are needed to prove the efficacy.…”
Section: Topical Immunotherapy In the Treatment Of Skin Diseasesmentioning
confidence: 99%
“…Topical medications such as imiquimod 5%, podofilox 0.5%, sinecatechins ointment 15% and diphenylcyclopropenone have been used in children with encouraging results. 1,4,5 Imiquimod is an immune stimulator that acts on the Toll-like receptors (TLRs)-7 and 8 and enhances production of interferons, tumor necrosis factor-α and interleukins-1, 6 and 8.…”
mentioning
confidence: 99%